2017
DOI: 10.3389/fpsyg.2017.01044
|View full text |Cite
|
Sign up to set email alerts
|

An Eye Tracking Study on the Perception and Comprehension of Unimodal and Bimodal Linguistic Inputs by Deaf Adolescents

Abstract: An eye tracking experiment explored the gaze behavior of deaf individuals when perceiving language in spoken and sign language only, and in sign-supported speech (SSS). Participants were deaf (n = 25) and hearing (n = 25) Spanish adolescents. Deaf students were prelingually profoundly deaf individuals with cochlear implants (CIs) used by age 5 or earlier, or prelingually profoundly deaf native signers with deaf parents. The effectiveness of SSS has rarely been tested within the same group of children for disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…In conjunction with this, CI users perceive the McGurk effect more often compared to normal hearing listeners (Stropahl, Schellhardt, and Debener, 2017 ). This benefit of visual information and increased perception of the McGurk effect could be due to CI users’ tendency to look at the mouth more compared to people with normal hearing (Mastrantuono, Saldaña & Rodríguez-Ortiz, 2017 ). People with CIs might look at the mouth more in order to help them get more information from the visual signal, in the face of auditory degradation.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with this, CI users perceive the McGurk effect more often compared to normal hearing listeners (Stropahl, Schellhardt, and Debener, 2017 ). This benefit of visual information and increased perception of the McGurk effect could be due to CI users’ tendency to look at the mouth more compared to people with normal hearing (Mastrantuono, Saldaña & Rodríguez-Ortiz, 2017 ). People with CIs might look at the mouth more in order to help them get more information from the visual signal, in the face of auditory degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Eye gaze tracking studies have observed that, during SL communication, signers maintain their gaze on the face of their interlocutor rather that looking at the hands of that individual (Agrafiotis, Canagarajah, Bull, & Dye, 2003;Emmorey, Korpics, & Petronio, 2009;Mastrantuono, Saldaña, & Rodríguez-Ortiz, 2017;Muir & Richardson, 2005). Subtle visual (phonological) distinctions (Siple, 1978) as well as grammatical markings (Brentari & Crossley, 2002;Elliott & Jacobs, 2013;Grossman & Kegl, 2007) that occur on the face of the signer, likely require signers to foveate the face to maintain the high levels of visual acuity required.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of a proper sign language model from birth is especially demonstrated by studies on deaf children with cochlear implants born from deaf parents. These children, exposed to an intact and fluent model of sign language, either American (Davidson, Lillo-Martin, & Pichler, 2014), Spanish (Mastrantuono, Saldaña, & Rodríguez-Ortiz, 2017) or Italian (Rinaldi & Caselli, 2014), develop age-appropriate spoken language skills.. The exposure to an intact model of sign language from birth also benefits the development of executive functions, as tested for French Sign Language (Courtin, 2000) and American Sign Language (Dye & Hauser, 2014;Hall, Eigsti, Bortfeld, & Lillo-Martin, 2017b;Schick, de Villiers, de Villiers, & Hoffmeister, 2007).…”
Section: Sign-supported Speech and Bilingual Approaches In The Educat...mentioning
confidence: 99%
“…Studies in that field indicate that deaf observers mainly foveate the face area. Deaf perceivers, both cochlear implant users and native signers, have been observed to look at the face more than 95% of the time when attending sign language (Spanish Sign Language), as well as when attending spoken language and SSS (Mastrantuono et al, 2017).…”
Section: Sign-supported Speech and Bilingual Approaches In The Educat...mentioning
confidence: 99%
See 1 more Smart Citation